Pastoral work of a military chaplain in the Armed Forces of Ukraine as psychological support for military serviceman: content and features - KYRYLENKO, Taisa; HORBYK, Ivan (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2024)
Background. It is established that pastoral work is a vital important component in nurturing the spiritual well-being of the Ukrainian soldier during the aggressive war with the Russian Federation. The goal was to emphasize the content of military chaplaincy and the findings of preliminary research into individual aspects of chaplain's activities. Considering the religious affiliations of most Ukrainians, chaplaincy efforts were examined from a Christian perspective.Methods. Theoretical methods used included analysis and generalization. For the empirical research, an author-designed questionnaire was administered to explore the psychological aspects of military chaplains' roles.Results. The analysis of the literature led to the development of a basic framework outlining the elements of pastoral work. A comparative analysis of the roles of military chaplains and military psychologists was conducted, identifying the boundaries of their respective competencies and the overlap in their activities. An author-led survey included 44 servicemen affiliated with military chaplaincy, representing varying lengths of service. The survey revealed the challenges faced in deciding to become a military chaplain, difficulties encountered in their work, and what support was beneficial to them.Conclusion. The chaplain can enhance the positive impact on personnel through collaboration with the psychologist at the intersection of their activities or by redirecting one's attention to improve the effectiveness in working with a special attention group, focusing on the recovery of servicemen after combat, treatment of PTSD, and other specialized functions. The most challenging aspects of a military chaplain's role include coping with personnel loss, establishing rapport with the command, and earning authority and trust. To address these issues, it was found that regardless of chaplaincy duration, 86% of the primary psychological resource is derived from "God and prayer to Him".
Keywords: personality; military chaplain; prayer; spirituality; psychological support; pastoral work; serviceman; family of a military serviceman